Systematic review on the impacts of community-based sheep breeding programs on animal productivity, food security, women’s empowerment, and identification of interventions for climate-smart systems under the extensive production system in Ethiopia - Tesfa, Assemu; Taye, Mengistie; Haile, Aynalem; Nigussie, Zerihun; Najjar, Dina; Mekuriaw, Shigdaf; Dijk, Suzanne V; Wassie, Shimels E; Wilkes, Andreas; Solomon, Dawit (Elsevier, 2025)
This systematic review was conducted to appraise the impact of community-based sheep breeding programs in Ethiopia on animal genetic improvement, household food security, women’s empowerment, and to identify integrative climate-smart interventions. The review includes 51 documents from databases such as PubMed, AJOL, CAB Direct, Web of Science, and Google Scholar, together with grey literature and institutional reports. Community-based breeding programs (CBBP) in Ethiopia provide a participatory approach that empowers farmers by addressing the limitations of crossbreeding and nucleus breeding programs. CBBP have brought significant improvements in growth and reproductive traits, food security, and women empowerment. Compared to baseline values, the intervention resulted in a 3.63 %, 5.6 %, 7.58 %, and 7.25 % improvement in birth weight, weaning weight, six-month weight, and yearling weight, respectively. Besides, litter size was improved by 0.09, and lambing intervals and age at first lambing were reduced by 21.31 days and 75.68 days, respectively. These gains has got translated into improved household livelihoods and food security through increased income from the sale of improved animals. Since 2019, seven women-led CBBPs comprising 486 members have been established, enhancing women’s participation in small ruminant breeding. For the implementation of small ruminant breeding, including CBBPs, 16 stakeholders with 34 linkages were identified. However, apart from research centers, kebele experts, and projects such as the International Center for Agricultural Research in the Dry Areas (ICARDA), most institutions have contributed little, largely due to unclear institutional frameworks. This gap has resulted in the malfunctioning of several CBBP villages. Despite notable achievements, the program continuous to face technical, financial, and institutional challenges persist. Strengthening CBBPs through the integration of climate-smart strategies remains critical for ensuring long-term sustainability and reducing greenhouse gas emissions.